Images of women in loveswept and valentine romance novels a comparative analysis - Abella, Mary Charlotte E.
"This study sought to find out the different images of women presented in Philippine and American romance novels, particularly in Valentine and Loveswept romances. Using content analysis, the researcher studied 28 novels: 14 titles from Valentine romances and 14 from Loveswept. The study covered the years from 1986 up to 1992. Analyzed were the age, civil status educational attainment, economic status, occupation roles, problems, means to solve problems, story situations and personality traits of the female characters. The researcher also attempted to determine if a trend has been developed over the years of publication and if the female characters are reflective of the women in Philippine and American societies. The researcher found out that there are considerable differences in the portrayal of women in Valentine and Loveswept romances. In Valentine romances, women generally belong to the middle-class and are more concerned with their families and with society's norms. They are dependent, conservative and self-sacrificing. In Loveswept romances, the women generally belong to the upper-middle class and are concerned with themselves and their careers. They are independent, strong-willed and career-minded. The researcher discovered no trend in the characterization of the female characters. The researcher also found that the female characters in the stories are patterned after the women in their respective societies."